Repercussion of corporate governance on the financial market - rachame, kahina (Milev Journal of Research and Studies, 2016)
The crises, collapses and scandals that institutions and economies experienced, especially after the collapse of the largest auditing company in the word who led to bankruptcy and effected several global financial markets, have contributed in the appearance of a new concept which is the Corporate Governance, this last that constitutes an adequate solution in order to increase the faith in the majority of transactions inside financial markets, especially after the appearance of misguidance in financial audit reports, in order to increase the importance of control systems and the accountancy inside the institutions that entered into financial markets. The corporate governance acts to augment the credibility of the accounting data especially that nowadays, the world focuses on direct types of financing, by relying on financial markets, especially after the increase of creating and adopting big projects and reaching the stage of efficient financial markets to finance the existing investments